Analysis and development of sipemas: community complaint applications using the rapid application development method - Eugenius Kau Suni; Denny Jean Cross Sihombing (Institute of Computer Science (IOCS), 2023)
This research investigates the implementation of the Rapid Application Development (RAD) method for creating the